Accuracy of Chest CT for Differentiating COVID-19 from COVID-19 Mimics - Sähn, Marwin-Jonathan; Yüksel, Can; Keil, Sebastian; Zeisberger, Marcel P.; Post, Manuel; Kleines, Michael; Brokmann, Jörg Christian; Hübel, Christian; Kuhl, Christiane K.; Isfort, Peter; Schulze-Hagen, Maximilian Franz (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose To determine the performance of radiologists with different levels of expertise regarding the differentiation of COVID-19 from other atypical pneumonias. Chest CT to identify patients suffering from COVID-19 has been reported to be limited by its low specificity for distinguishing COVID-19 from other atypical pneumonias (“COVID-19 mimics”). Meanwhile, the understanding of the morphologic patterns of COVID-19 has improved and they appear to be fairly specific.Materials and Methods Between 02/2020 and 04/2020, 60 patients with COVID-19 pneumonia underwent chest CT in our department. Cases were matched with a comparable control group of 60 patients of similar age, sex, and comorbidities, who underwent chest CT prior to 01/2020 for atypical pneumonia caused by other pathogens. Included were other viral, fungal, and bacterial pathogens. All 120 cases were blinded to patient history and were reviewed independently by two radiologists and two radiology residents. Readers rated the probability of COVID-19 pneumonia according to the COV-RADS classification system. Results were analyzed using Clopper-Pearson 95 % confidence intervals, Youden’s Index for test quality criteria, and Fleiss‘ kappa statistics.Results Overall, readers were able to correctly identify the presence of COVID-19 pneumonia in 219/240 (sensitivity: 91 %; 95 %-CI; 86.9 %–94.5 %), and to correctly attribute CT findings to COVID-19 mimics in 159/240 ratings (specificity: 66.3 %; 59.9 %–72.2 %), yielding an overall diagnostic accuracy of 78.8 % (378/480; 74.8 %–82.3 %). Individual reader accuracy ranged from 74.2 % (89/120) to 84.2 % (101/120) and did not correlate significantly with reader expertise. Youden’s Index was 0.57. Between-reader agreement was moderate (κ = 0.53).Conclusion In this enriched cohort, radiologists were able to distinguish COVID-19 from “COVID-19 mimics” with moderate diagnostic accuracy. Accuracy did not correlate with reader expertise.Key Points: Citation Format
Keywords: COVID-19; diagnostic accuracy; CT; atypical pneumonia